Evaluation Systems, Ethics, and Development Evaluation - Thomas, V. (2012)
After some 65 years of international development assistance, it is still difficult to show the effectiveness of aid in ways that are fully convincing. In part, this reflects inadequacies in the evaluation systems of the bilateral, multilateral, and global organizations that provide official development aid. Underlying these weaknesses often are a lack of adequate resources to carry out evaluation, insufficient harmonization of evaluation systems to allow aggregation and comparisons, and data limitations. Capacity constraints in both developing countries and aid organizations hinder the quality of evaluations. In addition, evaluation too frequently is not used by donor agencies or recipient countries to improve development effectiveness. All of these issues raise ethical concerns about the efficient use of donor resources, the opportunity costs for developing countries, and most important the effects on the intended beneficiaries of aid.